Six ways to leave unemployment - Pedro Portugal; John T. Addison (Institute for the Study of Labor (IZA), 2003)
This paper uses a unique Portuguese data set to examine the effect of unemployment benefit receipt and maximum duration of benefits on escape rates from unemployment. The focus is on the time profile of transitions out of unemployment. The novel aspect of the study resides in its identification of six destination states, namely, open-ended employment, fixed-term contracts, part-time work, government-provided jobs, self employment, and labor force withdrawal. Strong evidence of disincentive effects of the unemployment benefit system is reported. This result obtains both in general and for the various destination states, among which some marked behavioral differences are detected.
Keywords: J64; J65; 330; unemployment benefits; unemployment duration; competing risks; Arbeitslosigkeit; Arbeitslosenversicherung; Dauer; Arbeitsangebot; Ökonomischer Anreiz; Schätzung; Portugal